2012
DOI: 10.1021/ic301587f
|View full text |Cite
|
Sign up to set email alerts
|

A Homologous Series of First-Row Transition-Metal Complexes of 2,2′-Bipyridine and their Ligand Radical Derivatives: Trends in Structure, Magnetism, and Bonding

Abstract: The organometallic first-row transition-metal complexes [M(2,2'-bipy)(mes)2] (M = Cr (1), Mn (2), Co (4), Ni (5); 2,2'-bipy = 2,2'-bipyridine; mes = 2,4,6-Me3C6H2) were reacted with potassium and a suitable alkali-metal sequestering agent to yield salts of the anionic species [M(2,2'-bipy)(mes)2](-). The neutral parent compounds and their corresponding anionic congeners were characterized by single-crystal X-ray diffraction in [Cr(2,2'-bipy)(mes)2]·1.5C6H6, [Mn(2,2'-bipy)(mes)2], [Co(2,2'-bipy)(mes)2]·THF, [Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 83 publications
(55 reference statements)
16
76
0
Order By: Relevance
“…[a] See bond labeling scheme in Figure 6. [14] Similar linear correlations between ligand redox state and bond lengths have been documented by us [15,16,18] and others [19] for N,NЈ-coordinated (bpy) n and (tpy) n ligands. It has been shown that an experimental assignment of the ligand oxidation level in a given coordination compound can be made from high-resolution X-ray structures alone by using these correlations.…”
Section: Dft Calculationssupporting
confidence: 77%
“…[a] See bond labeling scheme in Figure 6. [14] Similar linear correlations between ligand redox state and bond lengths have been documented by us [15,16,18] and others [19] for N,NЈ-coordinated (bpy) n and (tpy) n ligands. It has been shown that an experimental assignment of the ligand oxidation level in a given coordination compound can be made from high-resolution X-ray structures alone by using these correlations.…”
Section: Dft Calculationssupporting
confidence: 77%
“…Thereby, it has been shown that the structural features of the central C-C bond within the bipyridine ligand can be a strong indicator of its redox state [32,34,35]. This has been showcased for four-coordinate [M(mes) 2 (bipy)] (mes = 2,4,6-trimethylphenyl), where reduction with potassium graphite in the presence of either 18-crown-6 or crypt.222 led to a mainly bipyridine-based reduction and formation of K{L}[M(mes) 2 (bipy)] (L = 18-crown-6 or crypt.222) [34,35].…”
Section: Synthesis and Structural Characterisationmentioning
confidence: 99%
“…The lengths of the central C-C bond of the bipyridine ligand increases slightly from 1.417(6) Å for chromium to 1.432(3) Å for cobalt. The C-C bond lengths are thereby in the range of ligated 2,2 -bipyridine radical anions within isolable complexes [32,34,35,40,41].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations